Milenium dalam Wahyu 20: Analisis Amilenialisme dalam Tradisi Teologi Reformed - Erlangga Saputra; Moritan Lambei (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article explores the meaning of millennials in Revelation 20:1–6 through the lens of amillennialism within the framework of Reformed theology. The millennium—the thousand-year period of Christ's reign—is a central issue in Christian eschatological discussions, giving rise to three main views: premillennialism, postmillennialism, and amillennialism. Using historical-theological hermeneutics as well as the study of literature, this paper examines the symbolic meaning of the book of Revelation and how it has been interpreted throughout the history of the church. The amillennial approach interprets that Christ has reigned spiritually since His resurrection through His presence in the church, and that the millennium is not a literal period in the future, but rather describes the present era of the church. This understanding rejects the view of a literal thousand-year kingdom and focuses on Christ's ongoing work on the world. Therefore, the proper interpretation of millennials influences.